Revitalization of the Sharia Economic Concept Based on Local Wisdom in the Economic Activity System of the Acehnese Community - Baihaqi Baihaqi; Abdul Hamid (Program Pascasarjana IAIN Langsa, 2026)
This study aims to analyze the reconstruction and repositioning of the mawah (traditional profit-sharing) and gala (traditional pawning) systems through the optimization of digital technology by MSMEs as an economic safety net in Aceh. Using a descriptive qualitative method with a case study and phenomenological approach, data were gathered through in-depth interviews with micro-economic actors, farmers, and MSME practitioners, alongside field observations and documentation studies. The results indicate that the micro-economic system in Aceh reflects an integration of socio-religious values. While mawah practices still exist as an equity-based social safety net, they are vulnerable to value erosion due to asymmetric information. Conversely, serious challenges are identified in contemporary gala practices, which have distorted into hidden usury (riba khafi) and land exploitation due to long-term fluctuations in gold standards. As a solution, MSME actors reposition these practices through digital storytelling strategies, wrapping local products in ethical supply chain narratives to reconstruct traditional trust into digital content accountability. The conclusion of this study formulates a new conceptual model that integrates local socio-religious values into the contemporary digital ecosystem. This study contributes to the discourse of Islamic distributive justice at the grassroots level by proving that digital infrastructure can be repositioned as a tool for cultural preservation and standardizing inclusive and sustainable micro-customary agreements.